Pendirian Perseroan Terbatas Perseorangan Serta Tanggung Jawab Hukum Pemegang Saham Berdasarkan Undang-Undang Cipta Kerja - Yuliana Duti Harahap; Budi Santoso; Mujiono Hafidh Prasetyo (Notarius, 2021)
he substance of Job Creation Law significantly changes law for establishment of Limited Liability Company (Ltd) in Indonesia, especially those regulated in Company Law. The legal issue in this article is the change in regulation on establishment of Ltd and legal responsibility of shareholders in an individual Ltd based on the Job Creation Law. The research method in this article is juridical normative. Changes in the arrangement for the establishment of Ltd in the Job Creation Law, namely: First, the addition of the exemption provisions that require Ltd to be established by 2 (two) or more persons, namely for Ltd that meet criteria for Micro and Small Enterprises. Second, the minimum capital arrangement for the establishment of a Ltd is removed and determined based on the founder's decision. Third, criteria for establishing Ltd for Micro and Small Enterprises are only using a statement of establishment, without going through notary deed. Fourth, founders and shareholders of Ltd for Micro and Small Enterprises are only private individuals. The responsibility of shareholders for an individual company criteria Micro and Small Enterprises based on the Job Creation Law are limited to paid-up capital.Keywords: Establishment, Limited Liability Company; Individual; Job Creation LawAbstrakSubstansi UU Cipta Kerja mengubah secara signifikan hukum pendirian PT di Indonesia khususnya yang diatur dalam UU PT. Isu hukum artikel ini adalah perubahan pengaturan pendirian PT serta tanggung jawab hukum pemegang saham dalam PT perseorangan berdasarkan UU Cipta Kerja. Metode penelitian dalam artikel ini adalah yuridis normatif. Perubahan pengaturan pendirian PT dalam UU Cipta Kerja yaitu: Pertama, penambahan ketentuan pengecualian yang mewajibkan PT didirikan oleh 2 (dua) orang atau lebih yaitu PT yang memenuhi kriteria untuk UMK. Kedua, pengaturan modal minimal untuk pendirian PT dihapus dan ditentukan berdasarkan keputusan pendiri PT. Ketiga, pendirian PT kriteria untuk UMK hanya menggunakan surat pernyataan pendirian, tanpa melalui akta notaris. Keempat, pendiri dan pemilik saham PT khusus untuk UMK hanyalah orang perseroangan. Tanggung jawab pemegang saham untuk perseroan perseorangan kriteria UMK berdasarkan UU Cipta Kerja hanya terbatas pada modal yang disetorkan.Kata Kunci: Pendirian; Perseroan Terbatas; Perseorangan; UU Cipta Kerja